2020
DOI: 10.1111/echo.14588
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of left ventricular global longitudinal strain in ST‐segment elevation myocardial infarction patients with extended pharmaco‐invasive strategy: A six months follow‐up study

Abstract: Aims and Objectives To evaluate left ventricular (LV) function by assessment of LV global longitudinal strain (GLS) in ST‐segment elevation myocardial infarction (STEMI) patients who underwent delayed fibrinolysis and coronary intervention (extended pharmaco‐invasive strategy), since LV function is one of the determinants of both immediate and long‐term outcomes. Methods Prospective study of consecutive STEMI patients who underwent extended pharmaco‐invasive strategy. The LV function was estimated using LV GLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…8 Manjunath et al showed that global longitudinal strain GLS estimated by speckle-tracking imaging provide more informative results when used. 9 They used SK in their work (88.5%) and resulted in preserved LVEF (53.12 ± 5.61) after a 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Manjunath et al showed that global longitudinal strain GLS estimated by speckle-tracking imaging provide more informative results when used. 9 They used SK in their work (88.5%) and resulted in preserved LVEF (53.12 ± 5.61) after a 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with other published data. 8,9,17 According to guidelines 2 and other studies, 18 it is better to reperfuse the occluded artery by PI approach than waiting for PPCI. In Beni-Suef city, PPCI is not available in many centers.…”
Section: Discussionmentioning
confidence: 99%
“…The American Society of Echocardiography's guidelines were followed for taking LV measures. [ 17 , 18 ] Left atrial diameter (LAD), left ventricular end-diastolic and end-systolic diameters (LVDD and LVSD in mm), interventricular septum (IVS), posterior wall (PW) thickness at end-diastole, and left ventricular mass indexed to body surface area (LVMI) were all measured using M-Mode echo with 2-D guidance [ 17 , 18 ] We used Simpson's biplane approach to determine the LV ejection percentage (EF%). The pulsed-wave Doppler was used to record the mitral inflow velocities in order to quantify the following parameters: isovolumetric, E/A ratio, peak early (E) and late (A) diastolic velocities, and deceleration time of E velocity (DT) and isovolumetric relaxation time (IVRT).…”
Section: Methodsmentioning
confidence: 99%
“…The GLS average (GLS-Avg) was calculated from 17 myocardial segments, from the 3 longitudinal planes, (apical 4, 2 and 3 long axis views) i.e., vertically and basal, mid, and apical, i.e. horizontally of the anterior, anteroseptal, inferoseptal, inferior, inferolateral, and anterolateral walls according to the current standards [ 18 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation